Urgensi Kriminalisasi Contempt of Court sebagai Penguatan Eksekusi Putusan Peradilan Tata Usaha Negara - Candra Perbawati; Nabila Firstia Izzati (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
The presence of the State Administrative Courts Judiciary as an administrative law enforcement institution for justice seekers, often encounter obstacles to the implementation/execution of judgments. The decision in question is in the context of the fictitious lawsuit is negative where the nature of the decision is already in Kracht. Against the verdict that already in kracht, State Administrative Courts officials as the losing party often do not want to comply with the content decision from the judges of the State Administrative Court. This can be caused by several factors such as The implementation of the execution arrangement is not clear, then the presence of administrative efforts that are felt is still not effective in creating a deterrent effect, as well as a lack of awareness from State Administrative Courts officials who losing and not wanting to comply with the order of the State Administrative Courts decision is the main obstacle. Problem is the lack of awareness of the obedient attitude can be due to the nature of the State Administrative Courts decision, which is basically upholding self-respect from the losing party. The act of not complying with the content State Administrative Courts decision can be included in the elements of the Contempt of Court act that is regulated in Law Number 14 of 1985 jo Law Number 5 of 2004 concerning Supreme Court. This can certainly have implications for the possibility of criminalization of officials State Administrative Courts for the consequences of the non-compliance.